Tracing the Lines of Power, Coloniality, and Neoliberalism in UNESCO’s Education for Sustainable Development Policy - Younes, Marwa; Nadler Gomez, Leticia (Journal of Contemporary Issues in Education, 2023)
This paper critically analyses a reflection paper commissioned by the United Nations Educational, Scientific and Cultural Organization (UNESCO) that proposes a future where we, humans, learn to coexist with the non-human world and thereby contribute to its preservation. The paper, titled Learning To Become With the World: Education for Future Survival, represents a response to previous unsuccessful Education for sustainable development (ESD) initiatives. Drawing on Carol Bacchi’s (2009), “What’s the problem represented to be?” method, our analysis sheds light on assumptions and silences and considers potentially conflicting interests among different actors in formulating the policy proposed by the paper. Through this critical approach to analysis, several crucial implications have emerged. We argue that the report lacks practical applicability by ignoring human complexities and diversity and does not pay enough attention to the potential important role Indigenous ways of knowing, learning, and teaching could play for education for sustainable development.